New Frontiers of Health Education: Exploring the Impact of Specialization as it Relates to Medical and Health Education and its Implications for Advancing Community Health - Johnston, Bruce; Laura, Ronald S. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
This paper examines specialization as one of the unexamined and “taken-for-granted” philosophical presumptions which underpin the practice of modern medicine and health education. We argue that this gratuitous acceptance of specialization as a foundational component of the medical enterprise has adverse ramifications for health education which impede the advancement of community health. We suggest that specialization has been crystallized as a paradigmatic heuristic that almost imperceptibly encodes other unexamined philosophical assumptions, which are conjointly responsible for the ineffectiveness of modern medicine in its efforts to stem the rising tide of degenerative disease epidemics, such as cancer, heart disease, diabetes, etc. Lest we be misunderstood, it is imperative to make clear that it is no part of our purpose to denigrate the many quite astonishing breakthroughs in the technology of modern medicine. Our objective is to be critically constructive by showing that in regard to control of the epidemic of chronic disease, the medical preoccupation with specialization is not necessarily the best use of resources, and may in fact be inimical to the goal of diminishing the pervasiveness of chronic degenerative disease.